Managing chronic pain in an age of addiction - Purvez, Akhtar (Rowman & Littlefield, 2018)
Chronic pain is challenging to treat in the face of an ongoing opioid crisis. Akhtar Purvez's authoritative account of pain management explores the complex and competing factors involved. He discusses approaches including advanced interventional procedures, non-opioid medications, physical therapy, and behavioral and psychologic support.